Designing mobile learning instruction for ESL context: a review of instructional designs - M. Rafiq, Karmila Rafiqah; Hashim, Harwati; Md Yunus, Melor (Universiti Teknologi MARA, 2023)
The emerging trend of education in embracing mobile learning is irrefutable. Mobile learning has become a panacea to unexpected situations such as the Covid-19 pandemic. Due to that, a lot of educators designed mobile learning instructions to cater to their students’ needs. However, the wide variety of instructional design models caused confusion and difficulties for educators, especially English as Second Language (ESL) educators, to design practical instructions via a mobile application. Therefore, this paper aims to review the instructional design models in creating a mobile appli-cation, particularly for language learning. Five instructional design models were reviewed, which include 1) Merrill’s Principles of Instruction Model, 2) Gagne’s Nine Events of Instruction Model, 3) The Kemp Instructional Design Model, 4) The ADDIE model, and 5) The ASSURE model. Each model has its strengths and weaknesses. From the review, each model is also suitable for specific contexts. This paper implied that instructional designs are crucial as they provide step-by-step guidelines for educators or content developers in creating the materials or tools for learning. With the aid of instructional design, a content developer could plan content creation systematically for a better learning outcome.